Integrating Green Technology And Environmental Engineering For Urban Resilience - Giawa, Jun Fajar Krisman; Harefa, Andrew Christover; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2025)
This study explores the integration of green technology and environmental engineering as a foundation for strengthening urban resilience in the face of rapid urbanization, climate change, and resource depletion. By analyzing the interaction between sustainable technologies, ecological systems, and adaptive infrastructure, this research identifies key strategies for building cities that are not only environmentally sustainable but also socioeconomically resilient. The methodology combines literature-based analysis, comparative case studies, and data evaluation from urban development programs that apply green innovations. Results indicate that green infrastructure—such as renewable energy systems, water recycling technologies, and eco-friendly building materials—significantly enhances the capacity of cities to withstand and recover from environmental stressors. Furthermore, environmental engineering plays a critical role in optimizing urban systems through the integration of smart waste management, energy efficiency measures, and climate-responsive design. The study concludes that achieving urban resilience requires a holistic framework that merges technological innovation with policy alignment, community engagement, and long-term sustainability goals.